1990
DOI: 10.1111/j.1745-4530.1990.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

MODELING the AVERAGE SHEAR RATE IN A CO‐ROTATING TWIN SCREW EXTRUDER

Abstract: A procedure similar to the one commonly used with mixers has been utilized to develop a model for estimating the shear rate in co-rotating twin screw extruders. Newtonian and non-Newtonian fluids were used to estimate the average shear rate for three screw configurations of a Baker Perkins (MPF-SOD) twin screw extruder. As would be expected, the shear rate was highly correlated to the screw speed. At a given screw speed, 30 forwarding paddles generate the highest rate of shear, followed by feed screws and sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Yousfi et al observed brittle behavior of the nanofilled polyethylene terephthalate/polyethylene (PET/PE) blends processed in TSE compared to the neat blend as a result of thermal degradation of the clay organomodifier during compounding [11]. Mohamed et al [12], Eise et al [13], and Altomare et al [14] all predicted that screw speed and throughput are the main variables affecting degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Yousfi et al observed brittle behavior of the nanofilled polyethylene terephthalate/polyethylene (PET/PE) blends processed in TSE compared to the neat blend as a result of thermal degradation of the clay organomodifier during compounding [11]. Mohamed et al [12], Eise et al [13], and Altomare et al [14] all predicted that screw speed and throughput are the main variables affecting degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Shear rate in an extruder can be used to evaluate viscous dissipation, which is a source of energy to cook the material in the extruder (Mohamed et al. 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A model was presented for estimating the average shear rate in corotating twin-screw extruder [56]. Newtonian and non-Newtonian fluids were used to estimate the average shear rate for three screw configurations of Baker Perkins (MPF-500) twin-screw extruder section with a range of screw speed (100-400 r/min).…”
Section: Food Extruder Heat Transfer Modelingmentioning
confidence: 99%